Robot-assisted radical cystectomy (initial experience) - B. G. Guliev; B. K. Komyakov; R. R. Bolokotov; D. M. Il’in (Вестник урологии, 2019)
Introduction. The main method of treating patients with muscle invasive bladder cancer remains radical cystectomy (RC). In recent years in RC along with open access are used laparoscopic and robot-assisted approaches.Purpose of research. Describe main steps of robot-assisted RC.Materials and methods. From June 2018 to November 2019 10 patients were underwent robot-assisted RC with intracorporeal orthotopic ileocystoplasty. There were 8 male, and 2 female. Age of patents ranged from 54 to 76 years. Body mass index was 25.6±4.5 kg/м2. Preoperative examination included USI and CT of abdomen and pelvis, lchest CT, laboratory analyses. Procedure performed in Tredelenburg position. RC included next steps: mobilization of distal part of ureters, posterior dissection of bladder, lateral dissection of the bladder, vesicle pedicle is clipped by Hem-o-Lok clips, dorsal venous complex stitch and dissection of the urethra.Results. No conversion to open surgeries. Operative time of RC ranged from 100 to 240 min (mean – 120 min). Blood loss volume ranged from 259 ml to 800 ml (mean 370 ml), and generally blood loss was noted during mobilization of a prostate and a dorsal venous complex. The haemotransfusion was carried out to 3 patients. Morphologic examination is revealed T2 stage in 6 patients, T3 in 4 patients. Three patients also had adenocarcinoma of prostate. Lymph nodes were negative in all patients.Conclusion. Robot-assisted RC is a mini-invasive method for treatment of patients with muscle-invasive bladder cancer. Stage-by-stage approach during performing RC allows to reduce time of operation and quantity intra-and postoperative complications.